1999
DOI: 10.1016/s0741-5214(99)70068-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of race on the treatment for peripheral arterial occlusive disease

Abstract: There is a marked racial disparity in the treatment of patients with PAOD that may be caused in part by differences in the severity of disease or disease distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 33 publications
(45 reference statements)
1
74
1
1
Order By: Relevance
“…76 Multiple other studies have also demonstrated increased rates of amputation for black and Hispanic compared with white subjects. [77][78][79][80] Although the burden of traditional atherosclerotic risk factors was also higher in minority patients, the increased risk of amputation was not entirely explained by the higher prevalence of risk factors.…”
Section: Atherosclerotic Vascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…76 Multiple other studies have also demonstrated increased rates of amputation for black and Hispanic compared with white subjects. [77][78][79][80] Although the burden of traditional atherosclerotic risk factors was also higher in minority patients, the increased risk of amputation was not entirely explained by the higher prevalence of risk factors.…”
Section: Atherosclerotic Vascular Diseasementioning
confidence: 99%
“…There seems to be no sex difference in relative risk of PAD for subsequent CVD mortality. 67,80 In summary, many factors related to development, outcome, and prevention of atherosclerosis in cerebrovascular, aortic, renal, and peripheral arterial territories are shared with coronary atherosclerosis. Important differences remain, as do gaps in semantics, such as terminology, and fundamentals, such as data on the true prevalence of intramural aortic hematoma.…”
Section: Atherosclerotic Vascular Diseasementioning
confidence: 99%
“…The incidence of amputation was much higher (5.0 versus 2.5 per 10,000) among blacks when compared with the white reference group, whereas the incidence of revascularization was much lower (4.0 versus 7.1 per 10,000) among blacks. While controlling for confounding variables, multivariate analysis of this data set revealed blacks were more likely (OR, 3.79; CI, 3.34-4.40) than whites to undergo amputation of the extremity [25].…”
Section: Differences In Rate or Risk Of Lower Extremity Amputationmentioning
confidence: 92%
“…Amputation is surgery that not only requires additional funds for rehabilitation, but also prosthetic creation, management, and maintenance [19,40]. Amputation also plays a major role in an individual's psychosocial, functional, and economic status, making it more difficult for a person to return to leisure, educational, and employment activities [25,42,50,57].…”
Section: Introductionmentioning
confidence: 99%
“…Black patients are more likely to undergo amputation and are less likely to undergo revascularization than are their white counterparts. 41 Many questions are unanswered with regard to the epidemiology and prognosis of subclinical disease; data have been collected in many community-based cohorts. The single-site or single-race/ethnicity design of most previous studies limits comparisons across racial/ethnic groups; the observed disparities may be attributable to variation in the performance or measurement of the subclinical disease in different centers as opposed to being attributable to ethnic differences.…”
Section: Multi-ethnic Study Of Atherosclerosismentioning
confidence: 99%